A seamless tube material for vehicle-mounted camera and preparation method thereof
By using seamless pipe materials prepared with specific ratios of 6061 aluminum alloy waste and reinforced particles, the existing vehicle-mounted camera materials have poor corrosion resistance and short service life, achieving higher weather resistance and service life, and reducing costs.
Patent Information
- Application Number
- CN202411265459.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The positive extruded 6063 small-sized seam pipe used in existing vehicle cameras leads to exposure of welds, low appearance quality, poor corrosion resistance, short service life, and high material loss rate, resulting in increased costs.
Seamless pipe materials are made of 6061 aluminum alloy waste, aluminum-silicon intermediate alloy, iron agent, copper plate, magnesium ingot, chromium agent, aluminum-titanium boron wire, aluminum ingot and single-wall carbon nanotubes, and are prepared through furnace smelting, refining, casting, homogenizing annealing and cutting and straightening.
It improves the strength, hardness and processing performance of seamless pipe materials, improves the weather resistance and service life of the on-board camera module, improves the user experience, and reduces the material loss rate and cost.
Smart Images

Figure BDA0005036996000000131 
Figure BDA0005036996000000132 
Figure BDA0005036996000000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of vehicle-mounted camera material preparation, and in particular to a seamless tube material for a vehicle-mounted camera and a preparation method thereof. Background Art
[0002] The seamless tube material in the car camera is usually used to make some structural parts of the camera, such as the outer shell or supporting structure to protect the lens. The main purpose of using seamless tubes is to enhance the stability and physical protection of the camera, prevent external environmental factors (such as dust and moisture) from entering the camera, and improve the structural firmness and pressure resistance. This is especially important for vehicle-mounted equipment because they need to withstand the vibration and impact generated during the vehicle's driving. Regarding the material, the seamless tube used in the car camera may be made of a variety of materials, depending on the design requirements and the use environment. Generally speaking, it includes but is not limited to the following materials: stainless steel, stainless steel has good corrosion resistance It has good properties and mechanical properties, suitable for various environmental conditions, especially performing well in humid or dusty environments; aluminum alloy, aluminum alloy is light and high-strength, easy to process and form, and has good corrosion resistance, suitable for application scenarios with strict requirements on weight; high-strength alloy steel, for applications requiring higher strength, specific types of alloy steel may be selected, such materials can provide higher strength and wear resistance; special plastics or composite materials, although not seamless pipe materials in the traditional sense, in some occasions, in order to reduce weight or reduce costs, high-performance plastics or composite materials may be used to replace metals, these materials can also achieve similar seamless effects through special processes.
[0003] At present, most of the vehicle-mounted monitoring cameras and rearview mirrors use small-sized 6063 seamed tubes that are extruded. After anodizing, the welds on the surface of the camera are exposed, and the appearance quality is low. In addition, the presence of the welds greatly reduces the corrosion resistance of the camera, and the weather resistance is poor. The life of the camera module is short, user maintenance is frequent, and the user experience is not good.
[0004] In addition, 6061 is one of the most widely used Al-Mg-Si deformed aluminum alloys in the aluminum processing field. It has medium strength, excellent extrusion process performance, is suitable for anodizing and has low sensitivity to stress corrosion cracking. It is the best choice as an aluminum alloy material for vehicle-mounted cameras. However, many vehicle-mounted cameras use solid 6061 bars as raw materials. Downstream manufacturers have a high material loss rate during machining, resulting in higher final product costs.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a seamless tube material for vehicle-mounted cameras and a preparation method thereof. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a seamless tube material for a vehicle-mounted camera and a preparation method thereof, so as to provide a 6061 aluminum alloy small-size seamless tube with higher anodized appearance quality, better mechanical properties, better weather resistance of the vehicle-mounted camera module, longer service life and better user experience.
[0007] Based on the above purpose, the present invention provides a seamless tube material for a vehicle-mounted camera and a preparation method thereof.
[0008] A seamless tube material for a vehicle-mounted camera, comprising the following raw materials in parts by weight: 900-920 parts of a mixture A and 600-620 parts of a mixture B;
[0009] The mixed material A comprises the following raw materials: 6061 aluminum alloy scrap A, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot, and reinforcing particles A;
[0010] The mixed material B comprises the following raw materials: 6061 aluminum alloy scrap B, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot, and reinforcing particles B;
[0011] The particle size ratio of the 6061 aluminum alloy scrap A and the 6061 aluminum alloy scrap B is 2-2.5:3-4;
[0012] The reinforcement particles A and the reinforcement particles B are both obtained by mixing single-walled carbon nanotubes and titanium carbide.
[0013] Preferably, the mass ratio of 6061 aluminum alloy scrap A, aluminum-silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum-titanium-boron wire, aluminum ingot and reinforcing particles A in the mixture A is 480-600: 12-13.2: 0.48-0.72: 1.08-1.2: 3.36-3.6: 0.12-0.36: 1.32-1.56: 339.6-342: 6-12.
[0014] Preferably, the reinforcing particles A are obtained by mixing single-walled carbon nanotubes and titanium carbide in a mass ratio of 0.285-0.571:5.714-11.428.
[0015] Preferably, the mass ratio of 6061 aluminum alloy scrap B, aluminum-silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum-titanium-boron wire, aluminum ingot and reinforcing particles B in the mixture B is 320-400: 8-8.8: 0.32-0.48: 0.56-0.8: 2.24-2.4: 0.08-0.24: 0.88-1.04: 226.4-228: 4-8.
[0016] Preferably, the reinforcing particles B are obtained by mixing single-walled carbon nanotubes and titanium carbide in a mass ratio of 0.19-0.38:3.81-7.62.
[0017] Preferably, the silicon content in the aluminum-silicon master alloy is 12%-18%, and the iron content in the 75 iron agent is 70%-80%.
[0018] Preferably, the copper content in the electrolytic copper plate is 95%-99%, and the magnesium content in the magnesium ingot is 95%-99%.
[0019] Preferably, the chromium content in the 75 chromium agent is 70%-80%, and the titanium content in the aluminum-titanium-boron wire is 4%-6%.
[0020] A method for preparing a seamless tube material for a vehicle-mounted camera, characterized in that it comprises the following steps:
[0021] Step S1. Smelting in a furnace: adding mixed material A and mixed material B into a smelting furnace to melt into molten aluminum, and stirring the molten aluminum at 730-755° C. to obtain mixed material C;
[0022] Step S2. Refining: Add a refining agent to the mixture C, refine for 25-30 minutes, let stand for 30-40 minutes, adjust the system temperature to 730-755°C, and obtain a mixture D;
[0023] Step S3. Casting: Casting the mixture D at a temperature of 650-725° C. and a casting speed of 95-105 mm / min into a rough cast rod;
[0024] Step S4. Homogenization annealing: stack the crude cast bars into a pile and place them into a homogenization annealing furnace for annealing at 550-570°C for 6-8h. After annealing, place them into a cooling furnace and spray water to cool them to room temperature to obtain aluminum alloy round cast bars;
[0025] Step S5. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0026] Beneficial effects of the present invention:
[0027] The invention provides a seamless tube material for a vehicle-mounted camera and a preparation method thereof. The invention divides 6061 aluminum alloy waste into 6061 aluminum alloy waste A and 6061 aluminum alloy waste B with different particle sizes, and then mixes the 6061 aluminum alloy waste A and 6061 aluminum alloy waste B with aluminum silicon intermediates, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot and reinforcing particles. Compared with the prior art, the seamless tube material prepared by the invention has higher strength, hardness and processing performance, and has broad application prospects. DETAILED DESCRIPTION
[0028] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0029] Embodiment 1: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0030] S1. 0.285 g of single-walled carbon nanotubes and 5.714 g of titanium carbide were mixed to obtain enhanced particles A;
[0031] S2. 480g6061 aluminum alloy scrap A, 12g of aluminum-silicon master alloy having a silicon content of 12%, 0.48g of 75 iron agent having an iron content of 70%, 1.08g of electrolytic copper plate having a copper content of 95%, 3.36g of magnesium ingot having a magnesium content of 95%, 0.12g of 75 chromium agent having a chromium content of 70%, 1.32g of aluminum-titanium-boron wire having a titanium content of 4%, 339.6g of aluminum ingot and 6g of reinforcing particles A were mixed to obtain a mixture A;
[0032] S3. 0.19 g of single-walled carbon nanotubes and 3.81 g of titanium carbide were mixed to obtain enhanced particles B;
[0033] S4. 320g 6061 aluminum alloy scrap B, 8g aluminum-silicon master alloy having a silicon content of 12%, 0.32g 75 iron agent having an iron content of 70%, 0.56g electrolytic copper plate having a copper content of 95%, 2.24g magnesium ingot having a magnesium content of 95%, 0.08g 75 chromium agent having a chromium content of 70%, 0.88g aluminum titanium boron wire having a titanium content of 4%, 226.4g aluminum ingot and 4g reinforcing particles B were mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B was 2:3;
[0034] S5. Furnace smelting: 900 g of mixture A and 600 g of mixture B were added to a smelting furnace and smelted into molten aluminum. The molten aluminum was stirred at 730 ° C to obtain a mixture C;
[0035] S6. Refining: Add a refining agent to the mixture C, refine for 25 min, let stand for 30 min, adjust the system temperature at 730 ° C, and obtain a mixture D;
[0036] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 650° C. and a casting speed of 95 mm / min;
[0037] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed into a homogenization annealing furnace, annealed at 550°C for 6 hours, and then placed into a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0038] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0039] Embodiment 2: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0040] S1. 0.29 g of single-walled carbon nanotubes and 6 g of titanium carbide were mixed to obtain enhanced particles A;
[0041] S2. 485g 6061 aluminum alloy scrap A, 12.2g aluminum-silicon master alloy having a silicon content of 13%, 0.5g iron content of 72% 75 iron agent, 1.1g copper content of 96% electrolytic copper plate, 3.4g magnesium ingot having a magnesium content of 96%, 0.16g chromium content of 72% 75 chromium agent, 1.36g titanium content of 5% aluminum-titanium-boron wire, 340g aluminum ingot and 7g reinforcement particles A were mixed to obtain a mixture A;
[0042] S3. 0.2 g of single-walled carbon nanotubes and 3.9 g of titanium carbide were mixed to obtain enhanced particles B;
[0043] S4. 330g 6061 aluminum alloy scrap B, 8.2g aluminum-silicon master alloy having a silicon content of 13%, 0.36g 75 iron agent having an iron content of 72%, 0.58g electrolytic copper plate having a copper content of 96%, 2.28g magnesium ingot having a magnesium content of 96%, 0.12g 75 chromium agent having a chromium content of 72%, 0.9g aluminum titanium boron wire having a titanium content of 5%, 226.8g aluminum ingot and 5g reinforcing particles B were mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B was 2.1:3.2;
[0044] S5. Furnace smelting: 904 g of mixture A and 604 g of mixture B were added to a smelting furnace and smelted into molten aluminum. The molten aluminum was stirred at 735 ° C to obtain a mixture C;
[0045] S6. Refining: Add a refining agent to the mixture C, refine for 26 min, let stand for 32 min, adjust the system temperature at 735 ° C, and obtain a mixture D;
[0046] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 655° C. and a casting speed of 98 mm / min;
[0047] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed into a homogenization annealing furnace for annealing at 555°C for 7 hours. After the annealing, the crude cast bars are placed into a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0048] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0049] Embodiment 3: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0050] S1. 0.32 g of single-walled carbon nanotubes and 7 g of titanium carbide were mixed to obtain enhanced particles A;
[0051] S2. 490g6061 aluminum alloy scrap A, 12.6g of aluminum-silicon master alloy having a silicon content of 14%, 0.52g of 75 iron agent having an iron content of 74%, 1.12g of electrolytic copper plate having a copper content of 97%, 3.5g of magnesium ingot having a magnesium content of 97%, 0.16g of 75 chromium agent having a chromium content of 74%, 1.36g of aluminum-titanium-boron wire having a titanium content of 5%, 340g of aluminum ingot and 8g of reinforcing particles A were mixed to obtain a mixture A;
[0052] S3. 0.22 g of single-walled carbon nanotubes and 5 g of titanium carbide were mixed to obtain enhanced particles B;
[0053] S4. 360g 6061 aluminum alloy scrap B, 8.4g aluminum-silicon master alloy having a silicon content of 14%, 0.38g 75 iron agent having an iron content of 74%, 0.62g electrolytic copper plate having a copper content of 97%, 2.28g magnesium ingot having a magnesium content of 97%, 0.12g 75 chromium agent having a chromium content of 74%, 0.94g aluminum-titanium-boron wire having a titanium content of 6%, 226.8g aluminum ingot and 6g reinforcing particles B were mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B was 2.2:3.4;
[0054] S5. Furnace smelting: 908 g of mixture A and 608 g of mixture B were added to a smelting furnace to melt into molten aluminum, and the molten aluminum was stirred at 740 ° C to obtain a mixture C;
[0055] S6. Refining: Add a refining agent to the mixture C, refine for 27 min, let stand for 34 min, adjust the system temperature at 740 ° C, and obtain a mixture D;
[0056] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 660° C. and a casting speed of 99 mm / min;
[0057] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed in a homogenization annealing furnace, annealed at 560°C for 8h, and then placed in a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0058] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0059] Embodiment 4: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0060] S1. 0.5 g of single-walled carbon nanotubes and 9 g of titanium carbide were mixed to obtain enhanced particles A;
[0061] S2. 560g6061 aluminum alloy scrap A, 12.5g of aluminum-silicon master alloy having a silicon content of 16%, 0.59g of 75 iron agent having an iron content of 77%, 1.13g of electrolytic copper plate having a copper content of 98%, 3.47g of magnesium ingot having a magnesium content of 96%, 0.25g of 75 chromium agent having a chromium content of 76%, 1.47g of aluminum-titanium-boron wire having a titanium content of 5%, 339.9g of aluminum ingot and 10g of reinforcing particles A were mixed to obtain a mixture A;
[0062] S3. 0.28 g of single-walled carbon nanotubes and 5.62 g of titanium carbide were mixed to obtain enhanced particles B;
[0063] S4. 370g 6061 aluminum alloy scrap B, 8.6g aluminum-silicon master alloy having a silicon content of 16%, 0.39g 75 iron agent having an iron content of 77%, 0.69g electrolytic copper plate having a copper content of 97%, 2.32g magnesium ingot having a magnesium content of 97%, 0.18g 75 chromium agent having a chromium content of 77%, 0.92g aluminum titanium boron wire having a titanium content of 5%, 227g aluminum ingot and 7g reinforcing particles B were mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B was 2.3:3.5;
[0064] S5. Furnace smelting: 915 g of mixture A and 615 g of mixture B were added to a smelting furnace and smelted into molten aluminum. The molten aluminum was stirred at 745 ° C to obtain a mixture C;
[0065] S6. Refining: Add a refining agent to the mixture C, refine for 28 min, let stand for 36 min, adjust the system temperature at 745 ° C, and obtain a mixture D;
[0066] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 710° C. and a casting speed of 98 mm / min;
[0067] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed into a homogenization annealing furnace for annealing at 560° C. for 7 h. After the annealing, the crude cast bars are placed into a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0068] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0069] Embodiment 5: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0070] S1. 0.561 g of single-walled carbon nanotubes and 10 g of titanium carbide were mixed to obtain enhanced particles A;
[0071] S2. 550g6061 aluminum alloy scrap A, 12.9g aluminum-silicon master alloy having a silicon content of 17%, 0.71g 75 iron agent having an iron content of 78%, 1.18g electrolytic copper plate having a copper content of 98%, 3.58g magnesium ingot having a magnesium content of 98%, 0.34g 75 chromium agent having a chromium content of 78%, 1.52g aluminum-titanium-boron wire having a titanium content of 5%, 341g aluminum ingot and 11g reinforcing particles A were mixed to obtain a mixture A;
[0072] S3. 0.36 g of single-walled carbon nanotubes and 7.52 g of titanium carbide were mixed to obtain enhanced particles B;
[0073] S4. 390g 6061 aluminum alloy scrap B, 8.7g aluminum-silicon master alloy with a silicon content of 17%, 0.46g 75 iron agent with an iron content of 78%, 0.7g electrolytic copper plate with a copper content of 98%, 2.38g magnesium ingot with a magnesium content of 98%, 0.22g 75 chromium agent with a chromium content of 78%, 1g aluminum-titanium-boron wire with a titanium content of 5%, 227g aluminum ingot and 7g reinforcing particles B are mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B is 2.4:3.8;
[0074] S5. Furnace smelting: 918 g of mixture A and 618 g of mixture B were added to a smelting furnace to melt into molten aluminum, and the molten aluminum was stirred at 750 ° C to obtain a mixture C;
[0075] S6. Refining: Add a refining agent to the mixture C, refine for 29 min, let stand for 39 min, adjust the system temperature at 750 ° C, and obtain a mixture D;
[0076] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 720°C and a casting speed of 100 mm / min;
[0077] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed into a homogenization annealing furnace for annealing at 565° C. for 7 h. After the annealing, the crude cast bars are placed into a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0078] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0079] Embodiment 6: A method for preparing a seamless tube material for a vehicle-mounted camera, comprising the following steps:
[0080] S1. 0.571 g of single-walled carbon nanotubes and 11.428 g of titanium carbide were mixed to obtain enhanced particles A;
[0081] S2. 600g6061 aluminum alloy scrap A, 13.2g of aluminum-silicon master alloy having a silicon content of 18%, 0.72g of 75 iron agent having an iron content of 80%, 1.2g of electrolytic copper plate having a copper content of 99%, 3.6g of magnesium ingot having a magnesium content of 99%, 0.36g of 75 chromium agent having a chromium content of 80%, 1.56g of aluminum-titanium-boron wire having a titanium content of 6%, 342g of aluminum ingot and 12g of reinforcing particles A were mixed to obtain a mixture A;
[0082] S3. 0.38 g of single-walled carbon nanotubes and 7.62 g of titanium carbide were mixed to obtain enhanced particles B;
[0083] S4. 400g of 6061 aluminum alloy scrap B, 8.8g of aluminum-silicon master alloy having a silicon content of 18%, 0.48g of 75 iron agent having an iron content of 80%, 0.8g of electrolytic copper plate having a copper content of 99%, 2.4g of magnesium ingot having a magnesium content of 99%, 0.24g of 75 chromium agent having a chromium content of 80%, 1.04g of aluminum-titanium-boron wire having a titanium content of 6%, 228g of aluminum ingot and 8g of reinforcing particles B were mixed to obtain a mixture B, wherein the particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B was 2.5:4;
[0084] S5. Furnace smelting: 920 g of mixture A and 620 g of mixture B were added to a smelting furnace and smelted into molten aluminum. The molten aluminum was stirred at 755 ° C to obtain a mixture C;
[0085] S6. Refining: Add a refining agent to the mixture C, refine for 30 min, let stand for 40 min, adjust the system temperature at 755 ° C, and obtain a mixture D;
[0086] S7. Casting: The mixture D is cast into a rough cast rod at a temperature of 725° C. and a casting speed of 105 mm / min;
[0087] S8. Homogenization annealing: The crude cast bars are stacked into a pile and placed in a homogenization annealing furnace, annealed at 570°C for 8 hours, and then placed in a cooling furnace and sprayed with water to cool to room temperature to obtain aluminum alloy round cast bars;
[0088] S9. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
[0089] Comparative Example 1:
[0090] In this comparative example, compared with Example 1, reinforcing particles A were not added during the preparation process of the seamless tube material for a vehicle camera, and the remaining steps and parameters were the same. This comparative example will not be repeated, and finally a seamless tube material for a vehicle camera was obtained.
[0091] Comparative Example 2:
[0092] In this comparative example, compared with Example 1, mixture A was not added during the preparation process of the seamless tube material for a vehicle camera, and the remaining steps and parameters were the same. This comparative example will not be repeated, and finally a seamless tube material for a vehicle camera was obtained.
[0093] Comparative Example 3:
[0094] Compared with Example 1, this comparative example only adjusts the amount of "mixture A" from "900g" to "300g", and replaces the amount of "mixture B" from "600g" to "1200g", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains a seamless tube material for a vehicle-mounted camera.
[0095] Comparative Example 4:
[0096] Compared with Example 1, this comparative example only adjusts the "particle size ratio of 6061 aluminum alloy scrap A and 6061 aluminum alloy scrap B" from "2:3" to "3:2", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains a seamless tube material for a vehicle-mounted camera.
[0097] Performance Test:
[0098] The seamless tube materials for vehicle-mounted cameras prepared in Examples 1 to 6 of the present invention were used to prepare seamless tubes for vehicle-mounted cameras, and performance tests were performed:
[0099] Compared with the weight of solid round bars of the same outer diameter, the weight of the seamless pipe prepared in the present invention is reduced by 0.31 kg, which significantly saves the cost of raw materials.
[0100] Density: Referring to GBT2997-1982 standard, the Archimedes drainage method was used to measure the bulk density of the samples prepared in Examples 1 to 8 and Comparative Examples 1 to 6. The analytical balance (AR224CN, Ohaus Instruments, Changzhou) used for the test had an accuracy of 0.0001. The specific process was as follows: First, each group of samples that had been ultrasonically cleaned were placed in an oven at 70°C and dried to constant weight. After being taken out and cooled, the mass of each group of samples in the air, i.e., dry weight, was measured; then, the suspended samples were placed in a vacuum dish and vacuumed for 30 minutes, and then the samples were immersed in deionized water and continued to be vacuumed for 30 minutes; finally, the samples were taken out and their floating weight in deionized water was measured first, and then taken out of the water, and the residual liquid on the surface was wiped off with laboratory cotton to measure its wet weight. The bulk density of the sample can be calculated by the following formula, and finally, the relative density ratio (%) of the seamless pipe material prepared in Examples 1 to 6 and Comparative Examples 1 to 4 to the solid round rod was recorded:
[0101]
[0102] Among them, ρ w is the density of deionized water, m1 and m2 are the dry weight and wet weight of the sample, respectively, and m3 is the buoyant weight of the sample in deionized water;
[0103] Referring to the standard "GB / T6893-2022 Aluminum and Aluminum Alloy (Rolled) Tubes", the tensile strength (MPa) and yield strength (MPa) of the seamless tubes prepared in vehicle Examples 1 to 6 and Comparative Examples 1 to 4, wherein the yield strength is the stress at which the non-proportional elongation is 0.2%, represented by Rp0.2;
[0104] Table 1 Summary of experimental results of Examples 1-6 and Comparative Examples 1-4
[0105]
[0106]
[0107] Data Analysis:
[0108] It can be seen from Table 1 that the seamless tube material for vehicle-mounted cameras prepared by the present invention has higher tensile strength, higher yield strength and higher relative density. This may be because in the present invention, the 6061 aluminum alloy waste is first crushed into 6061 aluminum alloy waste A and 6061 aluminum alloy waste B with different particle sizes, and then the 6061 aluminum alloy waste A and 6061 aluminum alloy waste B are respectively mixed with aluminum silicon intermediate, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot, and reinforcing particles, and finally the obtained mixture A and mixture B are mixed in a specific ratio, which can achieve The large and small particles are evenly mixed, which significantly improves the density of the final product. In addition, the single-walled carbon nanotubes and titanium carbide compound in the system can be used as reinforcements to prevent deformation during the load-bearing process of the product, and can well bear the role of transferring loads. In addition, the single-walled carbon nanotubes and titanium carbide can also effectively play a role of dispersion strengthening in the matrix, helping the matrix to resist deformation in practical applications and hindering the dislocation movement of the matrix. While improving the hardness of the final seamless pipe material, it can also effectively refine the crystal grains inside the system and strengthen it, thereby further improving the mechanical properties of the final seamless pipe material.
[0109] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0110] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A seamless tube material for a vehicle-mounted camera, characterized in that: The raw materials include the following parts by weight: 900-920 parts of mixture A and 600-620 parts of mixture B; The mixed material A comprises the following raw materials: 6061 aluminum alloy scrap A, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot, and reinforcing particles A; The mixed material B comprises the following raw materials: 6061 aluminum alloy scrap B, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot, and reinforcing particles B; The particle size ratio of the 6061 aluminum alloy scrap A and the 6061 aluminum alloy scrap B is 2-2.5:3-4; The reinforcement particles A and B are both obtained by mixing single-walled carbon nanotubes and titanium carbide; The mass ratio of 6061 aluminum alloy scrap A, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot and reinforcing particles A in the mixture A is 480-600: 12-13.2: 0.48-0.72: 1.08-1.2: 3.36-3.6: 0.12-0.36: 1.32-1.56: 339.6-342: 6-12; The reinforcing particles A are obtained by mixing single-walled carbon nanotubes and titanium carbide in a mass ratio of 0.285-0.571:5.714-11.
428.
2. The seamless tube material for vehicle-mounted cameras according to claim 1, characterized in that: The mass ratio of 6061 aluminum alloy scrap B, aluminum silicon master alloy, 75 iron agent, electrolytic copper plate, magnesium ingot, 75 chromium agent, aluminum titanium boron wire, aluminum ingot and reinforcing particles B in the mixture B is 320-400: 8-8.8: 0.32-0.48: 0.56-0.8: 2.24-2.4: 0.08-0.24: 0.88-1.04: 226.4-228: 4-8.
3. The seamless tube material for vehicle-mounted camera according to claim 2, characterized in that: The reinforcing particles B are obtained by mixing single-walled carbon nanotubes and titanium carbide in a mass ratio of 0.19-0.38:3.81-7.
62.
4. The seamless tube material for vehicle-mounted camera according to claim 1, characterized in that: The silicon content in the aluminum-silicon master alloy is 12%-18%, and the iron content in the 75 iron agent is 70%-80%.
5. The seamless tube material for vehicle-mounted camera according to claim 1, characterized in that: The copper content in the electrolytic copper plate is 95%-99%, and the magnesium content in the magnesium ingot is 95%-99%.
6. The seamless tube material for vehicle-mounted camera according to claim 1, characterized in that: The chromium content in the 75 chromium agent is 70%-80%, and the titanium content in the aluminum titanium boron wire is 4%-6%.
7. The method for preparing a seamless tube material for a vehicle-mounted camera according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1. Smelting in a furnace: adding mixed material A and mixed material B into a smelting furnace to melt into molten aluminum, and stirring the molten aluminum at 730-755° C. to obtain mixed material C; Step S2. Refining: Add a refining agent to the mixture C, refine for 25-30 minutes, let stand for 30-40 minutes, adjust the system temperature to 730-755°C, and obtain a mixture D; Step S3. Casting: Casting the mixture D at a temperature of 650-725° C. and a casting speed of 95-105 mm / min into a rough cast rod; Step S4. Homogenization annealing: stack the crude cast bars into a pile and place them into a homogenization annealing furnace for annealing at 550-570°C for 6-8h. After annealing, place them into a cooling furnace and spray water to cool them to room temperature to obtain aluminum alloy round cast bars; Step S5. Cut and straighten the aluminum alloy round cast rod to obtain a seamless tube material for a vehicle-mounted camera.
Citation Information
Patent Citations
Metal matrix composite material and preparation method thereof
CN117230330A
Aluminum alloy material, preparation method thereof and circuit control safety valve
CN117626071A
Preparation process of aluminum-based thin plate based on particle reinforced aluminum-based composite material waste
CN118371717A